2008
DOI: 10.1021/op800148y
|View full text |Cite
|
Sign up to set email alerts
|

The Suzuki−Miyaura Reaction under Mechanochemical Conditions

Abstract: As a model for a C−C-coupling procedure a Suzuki−Miyaura reaction has been studied under mechanochemical conditions. Important parameters influencing the yield of the reaction are the revolutions per minute, the milling time, and the material of the milling balls and beakers, as well as the size and number of milling balls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 29 publications
3
76
0
6
Order By: Relevance
“…[222] The system requires a stoichiometric amount of tetraalkylammonium salt but is both solvent-and phosphine-free. Recently, Ondruschka and coworkers [224] found that potassium carbonate (base) and sodium chloride Ondruschka also found that under ball milling conditions aryl bromides were more reactive than aryl iodides, which contrasts with Suzuki reactions in solvents. It was also found that the greater water content of the alumina, the greater the reaction.…”
Section: Scheme 18 An Example Of the Ball Milled Heck Reactionmentioning
confidence: 99%
“…[222] The system requires a stoichiometric amount of tetraalkylammonium salt but is both solvent-and phosphine-free. Recently, Ondruschka and coworkers [224] found that potassium carbonate (base) and sodium chloride Ondruschka also found that under ball milling conditions aryl bromides were more reactive than aryl iodides, which contrasts with Suzuki reactions in solvents. It was also found that the greater water content of the alumina, the greater the reaction.…”
Section: Scheme 18 An Example Of the Ball Milled Heck Reactionmentioning
confidence: 99%
“…62,70 However, there are also examples from the field of organic synthesis in which no influence was observed, which seems to indicate a product decomposition due to high energy. 60,66,72,73 Table 10.1 provides an overview of the materials for milling balls and milling vessels applicable for mechanochemical syntheses. Beside material density, the chemical resistance is also important for organic syntheses.…”
Section: Grinding Materialsmentioning
confidence: 99%
“…Based on our knowledge, some examples of the preparation of Pd supported catalysts by mechanochemical activation are reported in Table 8. [153] Examples in the literature also address the topic of using mechanochemical activation in solvent free SMC [154,155]. Cravotto et al have reported the use of a new catalyst, based on chitosan that is cross-linked with hexamethylene diisocyanate using Pd(OAc) 2 , in solid-state SMC with aryl chloride.…”
Section: Mechanochemical Activation Of Smcmentioning
confidence: 99%